Uma análise dos elementos que determinam os preços das terras rurais na região Centro Oeste do Estado do Paraná - Silva, Claudinei Chalito da (2020)
This dissertation discusses the issue of rural land prices and addresses the document called the Land Market Analysis Report (RAMT), prepared by the National Institute for Colonization and Agrarian Reform (INCRA). The analyses start from the assumption that the document brings deficiencies and needs improvement in the study of the variables that determine the prices, besides adding more theoretical basis in its methodology. For this analysis, a review is made about the theory of income and the characteristics of land as a different commodity. It is found that land is a commodity surrounded by complex issues, such as its ownership highly tied to political and economic power, monopoly and speculation. For the case study, a geographical delimitation formed by 31 municipalities adopted by INCRA was selected, called Regional Land Market (MRT) 5, located in the central region of the state of Paraná. The municipalities of this delimitation fall on municipalities in the Center South of Paraná, North Central, West of Paraná and Center West of the mesoregions of the Brazilian Institute of Geography and Statistics (IBGE). For the analysis of the variables, three quantitative variables were selected: the accesses, the size of the area and the agronomic quality of the rural properties. The data for the measurement of the variables come from the Regional Superintendence of INCRA in Paraná and include a series of surveys conducted in 2016 and 2018. The analyses found that the determination of land prices is entirely given by the established market and the constant increase in prices makes access to land more expensive and difficult for farmers with lower economic conditions, hindering the application of public policies. In the analyses for future studies, it was proposed the continuity the studies of the variables, since this study used only two data from the experiment. Finally, it was recommended to add some collection data in future studies, such as: the inclusion of the reasons why real estate is sold; a methodology for collecting information that will allow the calculation of the elasticity factor; the inclusion of data from family farms and leisure sites in specific typologies, and the measurement of the power of market agents in prices determination. Other recommendations from the management and methodology point of view were: to keep the technical teams continuous; to qualify the technical staff; to plan and define more adequately the collection of information.